Agency and its connection to a sociocultural perspective on teachers’ professional development: the lived experiences of five EFL teachers - Morales Jaramillo, Maria Antonieta (Kansas State University, 2021)
The purpose of this qualitative phenomenological study was to explore the influence that a professional development (PD) program in the United States grounded on a sociocultural theory had on teachers’ professional activities as teachers back in their home country. The study shared teacher perceptions of how and why the professional development strategies and activities applied during the program influenced teachers’ growth and changes. In this qualitative, phenomenological study the unit of analysis was the experience of five Ecuadorian English as a Foreign Language (EFL) teachers who were part of an international professional development program grounded in sociocultural theories. The interpretative phenomenological analysis examined participants’ experience emphasizing the interpretation of participants’ views about what they experienced. Using this approach participants presented their perspectives of their experiences while the researcher interpreted those stories (Saldaña, 2016). This study included the suggested steps of Saldaña’s (2016) approach to phenomenology: building data through focus groups, interviews, and a journal; creating a coding analysis; and formulating themes. The use of criterion sampling ensured the teachers had common experiences in the same professional development program. The data sources and criterion sampling provided a thick, rich description of information about the professional development experience. The essence of the phenomenon was structured (Creswell, 2007). The overarching question that guided this research was: In what ways do Ecuadorian EFL teachers describe their practices applicable to agency as a result of their participation in a longitudinal program of PD grounded in tenets of Sociocultural theory? Using the lens of the study’s research question as a framework for reviewing the initial categories from focus group sessions, individual interviews, and a journal, the following themes emerged in the study: Strength in Teacher Collaboration, Factors that Motivate Teacher’s Engagement in PD and Factors that Motivate Teacher’s Changes. Themes were ordered in alignment with the study’s research question. The data from this study found teachers perceived the PD program experience positive. The use of a sociocultural theory as base of the PD program enriched the program and made it significative for the participants by increasing a sense of confidence in their capabilities and enhancing changes in their attitudes, beliefs and philosophies that contributed to their growth and transformation in agent of change.
Keywords: Teacher agency; Sociocultural theory; Teacher professional development; Zone of proximal development (ZPD)